2004
DOI: 10.1021/jp036270w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu(OH)2 Nanowires at Aqueous−Organic Interfaces

Abstract: Cu(OH)2 nanowires have been successfully synthesized at the organic−aqueous interface by the interaction of the copper−bis(2-ethylhexyl) phosphate complex in the organic layer with NaOH in aqueous layer. The nanowires have an average length of 4 μm and are several nanometers in width. CuO nanowires and short wiskers are conveniently prepared through dehydration of Cu(OH)2 at high concentrations of NaOH under ambient conditions. Transmission electron microscopy and X-ray diffraction techniques have been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
74
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 43 publications
(62 reference statements)
2
74
0
Order By: Relevance
“…CuO has also been used in antimicrobial applications and in preparation of nanofluids [24,25]. Various CuO nanostructures through chemical method as well as Cu(OH) 2 nanowires have been synthesised for various practical applications [26,27]. In contrast to an n-type semiconducting metal oxide, CuO is a p-type semiconductor because of its narrow band gap of 1.2-1.9 eV, thereby facilitating easy jump of electrons from one energy level to another [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…CuO has also been used in antimicrobial applications and in preparation of nanofluids [24,25]. Various CuO nanostructures through chemical method as well as Cu(OH) 2 nanowires have been synthesised for various practical applications [26,27]. In contrast to an n-type semiconducting metal oxide, CuO is a p-type semiconductor because of its narrow band gap of 1.2-1.9 eV, thereby facilitating easy jump of electrons from one energy level to another [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…were prepared starting from single crystalline Cu 2 (OH) 2 CO 3 nanoribbons as precursors for sacrificial-template via heat treatments [36]. Song et al [37] reported a different approach to the preparation for CuO nanowires starting from Cu(DEHP) 2 complex is as follows. First, Cu(DEHP) 2 complex were generated at pH 6 by mixing 2:1 molar ratio of bis(ethylhexyl) hydrogen phosphate (HDEHP) and CuCl 2 in heptane and water.…”
mentioning
confidence: 99%
“…1 Among materials based on 3d transition metals, cupric oxide (CuO) is a narrow band-gap p-type semiconductor. 2,3 With the decrease in the crystal size, nanosized cupric oxide may exhibit unique properties, which can be significantly different from those of the bulk material. Nanoparticles of this compound are used in many important fields of science and technology such as gas sensors, heterogeneous catalysts and lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Furthermore the large fraction of surface area, excellent stability, low production cost and good electronic properties make nanosized CuO as a suitable compound for new studies to determine its applicability as a material of solar cells, in particular due to its photoconductivity and photochemical properties. [2][3][4][5][6][7][8][9][10][11][12][13] In addition, metal oxides such as CuO may be particularly valuable antimicrobial agents as they can be prepared with extremely high surface areas. 14 Therefore, in the past two decades great efforts have been made to prepare nanosized CuO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation